A Comparative Morphological and Anatomical Study of Juniperus communis L., J. sibirica Burgsd., and J. pygmaea K. Koch from Bulgaria - Tzenka Radoukova; Ivanka Semerdjieva; Valtcho D. Zheljazkov (Plants, 2024)
Of the six juniper species found in the Bulgarian flora, three of the species have controversial taxonomic positions. Juniperus pygmaea K. Koch and J. sibirica Burgsd. exhibit similar morphological characteristics to J. communis L. in terms of leaves and female cones (galbuli). This is one of the reasons why, in the recent taxonomic developments, J. pygmaea and J. sibirica were united in a common variety of J. communis, namely, J. communis var. saxatilis. However, such a grouping of species in the Flora of Bulgaria has not been adopted. This study aimed to evaluate the degrees of similarity or difference in the structure of the leaves, galbuli, seeds, and pollen of J. communis, J. sibirica, and J. pygmaea using the methods of comparative anatomy by light microscope (LM) and scanning electron microscopy (SEM) observations and complex morphological measurements. The working hypothesis of this study was that the three species would show a different degree of similarity with each other, which would clarify their taxonomic rank. The morphological parameters revealed differences between the length/width ratio of galbuli and seed length of the three species, while leaf characteristics (length and width) showed a stronger resemblance between J. sibirica and J. pygmaea. Furthermore, a greater distinction between the leaves and galbili of J. communis and J. sibirica was found. The SEM analyses showed variations in the seed shape and spermoderm among the three species. The shape of J. communis seeds was oval and elongated, while J. pygmaea seeds were pear-shaped, and J. sibirica seeds were triangular-rhombic. The length and height of striations were diverse on seed spermoderm in the three species. The epicuticular waxes of leaves, located on the tips of the anticlinal walls of the elongated epidermal cells in J. pygmaea and J. communis, were oval, while they formed raised comb-like crystals in J. sibirica. The morphological, anatomical, and SEM analysis affirmed the accepted taxonomic status of J. communis and J. sibirica as independent species within the Bulgarian flora. Based on most of the analyzed parameters, J. pygmaea exhibits significant similarity with J. sibirica. Additionally, the similar habitats of these two species support the determination of J. pygmaea as a variety or form of J. sibirica rather than J. communis (J. sibirica forma pygmaea).